East-West synthesis in Lermontov’s works and the history of an oriental motif in the poetry of 1810-1830 - Ходанен, Людмила (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
This article concerns the Eastern motif ―the horse and the rider in the desert‖. This motif appeared in French poetry (Millevoye and Lagrange) in connection with the translations of the Bedouin (desert arabs) poetry. Gradually, in the poetry by Zukovskij (Песнь араба над могилою коня), Pushkin (IX Imitation from the poetic cycle Подражания Корану), Mitskevich (Фарис), and Lermontov (Три пальмы), a metasubject was formed, with a synthesis of Eastern and Western motifs. The poets start with the imitation of the Eastern texts and then, in their poetry, they start to express the philosophical ideas of correspondence between the Eastern and Christian cultures as different forms of a civilization development.